Выражение : 4 (х+з у)^2+3(4 х -у)^2-52(х+у)(х-у) б) а^3 + 125 в^3-(а+5в)^3 решить уравнение: 3х^2 - 0,6х+0,03-3(х-0,1)(х+0,1)=0,6

acherevachanna acherevachanna    2   01.04.2019 03:10    0

Ответы
Kakazabra Kakazabra  28.05.2020 02:48

4 (х+з у)^2+3(4 х -у)^2-52(х+у)(х-у)=4(x+3y)(x+3y) + 3(4 х -у)(4 х -у)- (52x+52y) (x-y)= 4 x^2+6xy+9y^2+48x^2-8xy+y^2 - 52x^2-52y^2= -2xy-42y^2

 

3х^2 - 0,6х+0,03-3(х-0,1)(х+0,1)=0,6

3х^2 - 0,6х+0,03-3(х^2 -0.01)=0.6

- 0,6х+0,03 +0.03=0.6

- 0,6х= 0.6-0.06

- 0,6х=0.54

x=- 0.9

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра